Eco-physiological studies on horned poppy, (Glaucium spp.) - Getlawi, Ahmed O. M., author; Hughes, Harrison, advisor; Shahba, Mohamed, advisor; Wallner, Stephen, committee member; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.